Electronic and microscopic assessment of application of small disperse hydroxyapatite for sealing dentinal tubules (LLC "Endo Press", 2020)
According to one hypothesis, dentin sensitivity is due to the movement of fluid in the dentinal tubules and the displacement of odontoblasts, which is perceived by nerve receptors of the pulp. Elimination of symptom of limited hyper sensibility in case of the dentin caries and the prevention of its complications in children is in the use of means which seal dentinal tubules and in inactivating the nerve endings. In the experiment the extent of penetration of a small disperse hydroxyapatite (SD HA) at tubules of dentine of teeth was estimated. In artificially created carious cavities on a dentine about a pulp we placed the paste of SD HA and subjected it to influence of ultrasound of small intensity. By results of scanning electronic microscopy of cuts of teeth it is established that SD HA provides a reliable sealing tubules of dentine and it can be applied as one of means to removal of a symptom of sensitivity of a tubules of dentine and prevention of complications of treatment of initial pulpitis.